A Good Night’s Sleep: A Narrative Review from Islamic Perspectives in Relation to Modern Sciences - Mohamad Nor, Zaswiza; Nabilah Yusoff, Nurul; Fakhrol Razi, Fasiha Ruhila; Sanusi, Nurul Atiqah (IIUM Medical Journal Malaysia, 2018)
As a biological universal, it is easy to overlook the degree to which culture and religion shape how people sleep, and how quality sleep is conceptualized. In the Western world, sleep hygiene tips are important for an individual to get “a good night’s sleep”. Meanwhile, sleep is also important from an Islamic perspective, which, the Quran and Hadith discuss on its types, importance and quality practices. In modern sciences, sleep deprivation is regarded as a significant health issue, however from an Islamic point of view, long sleep hours alone do not determine the efficiency of sleep, but rather it depends on various other factors and follows the sleeping etiquettes of Prophet Muhammad (PBUH). This narrative review was conducted to highlight sleep from Islamic perspectives in relation to modern sciences. Selected articles discussing sleep from Islamic perspectives and modern sciences were reviewed and summarized. These articles were retrieved from searches of computerized databases and search engines using keywords “Sleep from Islamic perspective”, “Sleep in modern science”, “Sleep hygiene”, “Western world and sleep”, “Sleep deprivation” and “Quality sleep”. A number of six studies were selected (n=6). Analyses found that a productive Muslim sleep routine is divided into three parts; one-third, respectively, for Allah, ourselves and sleep. Sleep hygiene was emphasized and discussed from the Islamic perspectives and the relation with modern sciences: performing ablution and supplicate before sleep, could prepare the body for a deep sleep; dusting the bed before sleep, would get rid of insects that lead to scabies; turning-off lights before sleep to maintain dark environment, could prevent disruption to normal circadian rhythms; early bedtime and early wake-up time, would ensure adequate sleep thus lower the risk of getting chronic diseases; washing the hands after waking -up would get rid of germs accumulated during sleep; and, lying down on the right side is to prevent snoring and to avoid the heart under pressure of the right lung (if lying on the left side). People should not abandon sleep as an important requirement. What has been described in the Quran and Hadith are corresponded with sleep hygiene as identified by modern sleep scientists. Prophet Muhammad (PBUH) also stressed the importance of sleep for good health, and in the Quran, sleep is described as a blessing from Allah and stressed the importance of the alteration of night and day.